Reverse vaccinology-based design of multivalent multiepitope mRNA vaccines targeting key viral proteins of Herpes Simplex Virus type-2 - Suneesh, N. S.; Dhotre, Kishore; Mahajan, Pratik; Dass, Debashree; Banerjee, Anwesha; Siddiqi, Nikhat J.; Malik, Abdul; Joshi, Manali; Khan, Abdul Arif; Nema, Vijay; Mukherjee, Anupam (Frontiers in Immunology, 2025)
IntroductionHerpes Simplex Virus type 2 or HSV-2 is a major cause of genital herpes, contributing to increased susceptibility to HIV, encephalitis, and other severe complications. Despite the availability of antiviral therapies such as acyclovir, their effectiveness is limited due to resistance and side effects, emphasizing the urgent need for an effective vaccine.MethodsThis study employed reverse vaccinology and immunoinformatics to design five multivalent, multiepitope mRNA vaccine constructs targeting HSV-2. Four key viral proteins—Glycoprotein B (gB), Ribonucleoside-diphosphate Reductase large subunit (RIR1), Infected Cell Protein 0 (ICP0), and VP23—were selected based on their roles in viral replication and immune evasion. Epitopes for Cytotoxic T Lymphocytes (CD8+), Helper T Lymphocytes (CD4+), and B cells were predicted and rigorously filtered for antigenicity, non-toxicity, and cytokine induction. Vaccine constructs were designed incorporating 50S ribosomal protein, Human β-defensin 3, and PADRE as adjuvants to enhance immune responses. Structural validation, molecular docking, codon optimization, and physiochemical analysis were performed to assess stability and immunogenic potential.ResultsThe vaccine constructs demonstrated favorable physiochemical properties, structural stability, and high antigenicity. Molecular docking revealed strong binding affinities between the predicted epitopes and their respective MHC class I and class II alleles. Proteasomal cleavage analysis confirmed efficient antigen processing, while codon optimization ensured compatibility with the human translational machinery. Computational immune simulations predicted a strong humoral and cellular immune response, including high IgG and IgM levels, robust CD4+ and CD8+ T-cell activation, and cytokine production.ConclusionThe rationally designed multiepitope mRNA vaccine constructs exhibit strong antigenic potential, structural stability, and immune-stimulatory properties, positioning them as promising candidates for HSV-2 vaccine development. These findings offer a novel, safe, and effective approach to HSV-2 immunization, warranting further experimental validation and preclinical studies.